Photoactivable peptides for identifying enzyme-substrate and protein-protein interactions. - Rotili, D; Altun, M; Hamed, R; Loenarz, C; Thalhammer, A; Hopkinson, R; Tian, Y; Ratcliffe, P; Mai, A; Kessler, B; Schofield, C (2011)
Photoactivated cross-linking of peptides to proteins is a useful strategy for identifying enzyme-substrate and protein-protein interactions in cell lysates as demonstrated by studies on the human hypoxia inducible factor system.